Bioscience Subjects Background and Nursing Education - Malik, Rozia; Hussain, Muhammad; Sarwer, Hajra; Afzal, Muhammad; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Traditionally, Nursing students study human bioscience e.g. pathophysiology, microbiology, anatomy and physiology in their first and second year course. Nursing students are facing difficulties with bioscience learning. Hence, it’s essential for nursing students to keep in mind that bioscience understanding is very important throughout the research, and clinical practice. The PURPOSE of this study was to assess BSN students’ experiences regarding bioscience subject’s background and nursing education. A cross-sectional analytic study was done among 183 BSN (Generic) students February 2018 to May 2018. Convenient sampling technique was used to collect the required sample size. Data on individual characteristics of Bioscience learning experiences was collected by distributing semi-structured questionnaire. Statistical tool SPSS 21.0 was used for the analysis of collected data. Person correlation test used to determine the relationship between variables. In this study majority of BSN (Generic) students were considered bioscience subjects more challenging and time consuming. About 45.36% participants were agreed with there is more content required for bioscience compared with nursing subjects. BSN students (59.56%) were reported that bioscience related to nursing practice to gain better understanding for assessment. Majority of participants were reported that bioscience subjects more difficult as compared to nursing subjects. Bioscience relationship with nursing practices significantly correlated with clinical-relevant employment. In this type of research the area of improvement have been reviewed further knowledge available for those who will conduct the research on this topic in future. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 163-169